Economic Growth, Gaps and Poverty of the Development in Makassar City During the Covid-19 Pandemic - Mustari Mustari (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was designed to determine the effect of COVID-19 on economic growth, inequality and poverty in Makassar. This research was conducted qualitatively before being described descriptively. Researchers use phenomenological methods in their investigations. The input pooling approach used in this research is interviews. The resource persons in this research were housewives affected by COVID-19 in the Makassar area. The technique for determining informants in this study uses the purposive sampling method. The validity test technique in this research uses a data triangulation validity test, namely method triangulation and source triangulation. After conducting qualitative exploration, it was found that (1) The impact of COVID-19 greatly affected the economy or small business income; (2) As for the decline in customers, layoffs have caused unemployment to rise drastically; (3) Uneven growth and poverty.